Psychosomatic-psychotherapeutic treatment in an evening clinic: a qualitative examination of patients’ expectations and experiences - Brunner, Friederike; Dinger, Ulrike; Friederich, Hans-Christoph; Schauenburg, Henning; Herzog, Wolfgang; Nikendei, Christoph (International journal of mental health systems, 2019)
Over a course of 10 weeks the psychosomatic-psychotherapeutic evening clinic at the University of Heidelberg offers an intensive and multimodal 3-h treatment program on three evenings a week. The clinic aims at accommodating patients who on the one hand do not fit the criteria of partial or full-time inpatient therapy, but on the other hand requires a more intensified therapy dose than the usual German outpatient settings can cater for. In the presented monocentric, qualitative study, we wanted to examine this treatment concept with regard to the patients’ specific concerns, expectations, and individual experiences. By contrasting differences in intensity of outpatient and inpatient treatment, we aimed to identify those characteristics of the evening clinic setting that were perceived as especially helpful.
Gesehen am 11.03.2020